The impact of self-transcendence values on cooperative behaviors: attitude mediation and emotional moderation - Kong, Qian-Qian; Baharum, Harmi Izzuan Bin (Frontiers in Psychology, 2026)
This study investigated the psychological mechanisms through which Self-transcendence values (ST), Emotional Intelligence (EI), and Foreign Language Enjoyment (FLE) influence cooperative behaviors among Chinese university-level English learners (N = 561). The results, analyzed using structural equation modeling (SEM), provided strong support for a “Value-Attitude-Behavior” (VAB) model. Specifically, ST was a significant positive predictor of cooperative attitudes, which in turn served as a key mediator in facilitating cooperative behaviors. Both EI and FLE were found to be significant positive contributors to cooperative attitudes and behaviors. A notable finding was that EI and FLE exhibited significant negative moderating effects on the relationship between ST and cooperative attitudes, indicating a non-linear, inhibitory role in the value transmission pathway. This study validates and extends the applicability of the VAB model to the domain of second language acquisition, highlighting the complex interplay between personal values and affective factors in shaping cooperative outcomes.